2014
DOI: 10.4025/actascianimsci.v36i2.22557
|View full text |Cite
|
Sign up to set email alerts
|

<b>Threonine-lysine ratio on the requirements of digestible lysine in diets for broilers

Abstract: ABSTRACT.Two experiments were performed to determine the influence of threonine-lysine (Thr:Lys) ratio on requirements of digestible lysine (Lys) in low crude protein diets for broilers in the growth phase. In the first experiment, a total of 480 Cobb 500 male broilers were distributed in a completely randomized experimental design with four dietary Thr:Lys ratio (57.0; 60.5; 64.0 and 67.5%) and with five replicates of 24 birds each. No significant differences were reported in weight gain, feed intake, poultry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Rossoni et al (2008) also reported a negative effect of excessive dietary threonine on pig feed intake and fat deposition. Ospina-Roja et al (2014) attributed the worse performance observed in 22-to 42-d-old broilers fed digestible Thr:Lys ratios higher than 57% to impaired protein synthesis caused by dietary amino-acid imbalance. According to those authors, the deamination of threonine excess relative the other amino acid into uric acid requires energy, which consequently impair animal performance.…”
Section: Resultsmentioning
confidence: 99%
“…Rossoni et al (2008) also reported a negative effect of excessive dietary threonine on pig feed intake and fat deposition. Ospina-Roja et al (2014) attributed the worse performance observed in 22-to 42-d-old broilers fed digestible Thr:Lys ratios higher than 57% to impaired protein synthesis caused by dietary amino-acid imbalance. According to those authors, the deamination of threonine excess relative the other amino acid into uric acid requires energy, which consequently impair animal performance.…”
Section: Resultsmentioning
confidence: 99%
“…Threonine has been extensively investigated and reviewed since feed grade l -Thr has been available worldwide. Researchers have recently updated the Thr requirements and recommended higher dietary levels than previously suggested for modern broilers, especially in the starter phase ( Dozier et al., 2015 ; Mehri et al., 2014 ; Ospina-Rojas et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%